A comparative study between CAMELS andAltmanmodels (Applied Study onBEMO Bank) (Damascus University Journal for the economic and Political sciences, 2023)
The research aims at introducing the CAMELS and ALTMAN model and its formulation, and studying the differences between the two models by applying them to BEMO Bank.The CAMELS model has yielded realistic results and takes into account considerably all aspects of banking performance both in terms of financial structure, profitability, liquidity, management and the impact on asset quality. And that the ALTMAN model has given results close to reality and to some extent take into account all aspects of banking performance whether in terms of financial structure, mainly profitability and employment rate, but did not take into account the impact of high negative rates such as the cost of income and the default rate.The most important recommendations: The researcher recommends the adoption of the CAMELS model in measuring the performance of the bank because it includes multiple aspects of the indicators of bankingperformance.
Keywords: CAMELS; ALTMAN; Bank Performance; Rating